RIPARIAN VEGETATION IN THE JOSÉ COLOMO RANCHERIA (EL MANGO) OF CIUDAD PEMEX, MACUSPANA, TABASCO - Morales Ramón, Isela; García García, Manuel Antonio; Cappello García, Silvia (Kuxulkab’, 2023)
The arboreal vegetation established on the banks of any body of water brings multiple benefits to the rest of the species, including humans. Such is the case of Ranchería José Colomo established on the bank of the Chilapa River, where tree species have been used for diverse activities. The purpose of the research was to determine the flora still present on the riverbank and the impact generated by the residents on the same vegetation. Height and diameter at breast height were recorded for each specimen. The results showed a low species richness. Also a higher number of specimens with small sizes concerning height and diameter. The species known as willow stood (“Salix humboldtiana”) out as predominant in the site, being protected by the locals due to the benefits it provides them.